TRANSFORMASI SISTEM PENDIDIKAN ISLAM KLASIK DALAM PEMBINAAN ULAMA DAN INTELEKTUAL MUSLIM - Jaenudin, Neng Julia; Neng Julia; Mahfud; Dwi Ariyanto; Muhamad Shoheh; Rumbang Sirojudin5 (Fakultas Agama Islam, 2026)
The transformation of the classical Islamic education system is a dynamic process that plays an important role in producing generations of influential Muslim scholars and intellectuals throughout Islamic history. This study aims to analyze the changes and developments of the Islamic education system from the classical period to its relevance in shaping modern Muslim intellectuals. The research method used is library research with a historical-philosophical approach, examining primary and secondary sources related to educational institutions such as kuttab, mosques, madrasahs, and Bayt al-Hikmah. The research results show that the classical Islamic education system underwent significant transformations in curriculum aspects, learning methods, and the role of educational institutions in shaping students' character and knowledge. Islamic education in the classical period did not only emphasize religious aspects, but also the rationality and universal knowledge that gave birth to great figures such as Al-Farabi, Al-Ghazali, and Ibn Sina. The relevance of this transformation in the modern era is seen in efforts to integrate religious knowledge and science within contemporary Islamic education systems to cultivate perfect human beings who are knowledgeable, ethical, and contribute to the advancement of the community.